PROFIL PROTEIN BERBASIS SDS-PAGE PADA ULAT SAGU HASIL PENGERINGAN DENGAN GARAM DAN TANPA GARAM - Aufit Fahima; Ana Hidayati Mukaromah; Stalis Norma Ethica (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Sago larvae is a potential source of animal protein because it is easy to digest, but it has a weakness, which is easy to rot. To avoid decay can be preserved by drying and salting the sago larvae. The purpose of this study was to determine the protein profile of the sago larvae which was dried with salt and without salt based on SDS-PAGE. The research sample used sago larvae with treatment:, 1) heated in oven with salt and 2) without salt, and also 3) salted without drying at 50 °C using an oven for 1 hour. The results of the study were obtained in the control of 26 bands and there were 6 major bands and 20 minor bands. In samples dried at 50°C using an oven for 1 hour without salting has 21 bands and  there  are  4  major  bands  and  17  minor  bands.  In  the  salted  sample concentration of 10% (b/b) for 1 hour it had 24 bands and there were 5 major bands and 19 minor bands. While the samples were dried and salted with a concentration of 10% (b/b) at a temperature of 50°C using an oven for 1 hour had 19 ribbons and there were 3 major bands and 16 minor bands. Based on the results of this study, the preservation of sago larvae by salting of 10% (b/b) is more recomended better than heating by oven for 1 hour at 50°C. In the salting  preservation,  number  of  protein  bands  of  sago  larvae  based  on  its protein profile decreases less than that in heating preservation . Keywords : Sago larvae, Drying, Salting, Protein Profile, SDS-PAGE.